REFORMASI BIROKRASI PUBLIK DALAM PERSPEKTIF GOOD GOVERNANCE - Rakhmat . (Jurnal Paradigma (JP), 2017)
Bureaucracy reform meant as a reform process through system transformation of bureaucracy governance. It was intended to create the public services more efficient and professional. Furthermore, bureaucracy reform strategy was directed to endorse the better changes of system, structure, culture, and human resources, especially the mindset of whole public officials in any kind government level. Citizen trust in government has been declining for more than several years now, public accountability has been proposed as a way to repair bureaucracy performance in order to create good governance in the frame of public administration reform